The use of nitrous oxide 'cracking' technology in the labour ward: a case report and patient account. Issue 2 (15th September 2022) - Khan‐Perez, J.; MacCarrick, T.; Martin, F.
Summary: Nitrous oxide is a common choice of labour analgesia in many countries. However, its use is associated with significant cost to the environment as well as potential risks of long‐term occupational exposure. Our hospital is one of a small number of healthcare providers in the United Kingdom trialling technology which catalytically destroys ('cracks') nitrous oxide to reduce greenhouse gas emissions and occupational exposure. When used in the setting of inhaled analgesia, cracking technology relies on capturing the patient's exhaled breath via a facemask or mouthpiece, a technique which requires some user skill and may be challenging for patients. In this report, we present the case of a primiparous 35‐year‐old consultant anaesthetist, who used nitrous oxide cracking technology with inhaled nitrous oxide analgesia (via a facemask) during labour. We present the patient's experiences and discuss the implications of using such technology on ambient nitrous oxide levels in the delivery room. Notably, despite this patient's professional expertise and familiarity with facemask use, nitrous oxide remained detectable throughout her labour, although generally at low levels. This illustrates that whilst this technology has the potential to reduce ambient nitrous oxide levels, its efficacy may vary depending on how it is used, with implications for patient education and support.